Hepatocyte Notch Signaling Deregulation Related to Lipid Metabolism in Women with Obesity and Nonalcoholic Fatty Liver. Issue 8 (13th July 2020) - Auguet, Teresa; Bertran, Laia; Binetti, Jessica; Aguilar, Carmen; Martínez, Salomé; Guiu‐Jurado, Esther; Sabench, Fàtima; Adalid, Laia; Porras, José Antonio; Riesco, David; Del Castillo, Daniel; Richart, Cristóbal
Abstract : Objective: This cohort study aimed to explore the relationship between the Notch signaling pathway and the degree of nonalcoholic fatty liver disease (NAFLD). Moreover, this study intended to investigate whether this pathway is related to hepatic lipid metabolism and Toll‐like receptors (TLRs). Methods: This study used real‐time polymerase chain reaction analysis to evaluate the hepatic expression level of all genes studied (Notch receptors NOTCH1, NOTCH2, NOTCH3, and NOTCH4, transcription factors HES 1 and HES5, and Hes‐related repressor proteins HEY 1 and HEY2 ) in hepatic tissue from two cohorts: women with severe obesity ( n = 57) and normal liver structure ( n = 20) or NAFLD ( n = 37). Results: In women with severe obesity and NAFLD, this study found downregulation of hepatic HES5 expression. This expression correlated positively with the hepatic expression of HES1, HEY1, and N OTCH 3 . This study also found a positive correlation between HES5 expression and sterol regulatory element–binding protein 1c ( SREBP1c ) and between N OTCH 3 and several genes related to hepatic lipid metabolism (encoding liver X nuclear receptor α variant 1, farnesoid X nuclear receptor, SREBP1c, acetyl–CoA carboxylase 1, fatty acid synthase, peroxisome proliferator–activated receptor α, carnitine palmitoyltransferase 1, carnitine O ‐octanoyltransferase, ATP‐binding cassette subfamily A member 1, and ATP‐binding cassette subfamily G member 1). Finally, this study found a positive correlation between N OTCH 2 and TLR2, TLR4, and TLR9 and a positive relationship between N OTCH 1 and TLR9 . Conclusions: Taken together, these findings suggest that hepatic expression of Notch proteins and ligands in relation to lipid metabolism pathways in the liver could have a role in NAFLD pathogenesis.